Cholinergic properties of new 7-methoxytacrine-donepezil derivatives - Sepsova, Vendula; Karasova, Jana Z; Tobin, Gunnar; Jun, Daniel; Korabecny, Jan; Cabelova, Pavla; Janska, Katerina; Krusek, Jan; Skrenkova, Kristyna; Kuca, Kamil; Soukup, Ondrej (General physiology and biophysics, 2015)
Organophosphorus nerve agents inhibit acetylcholinesterase (AChE) which causes the breakdown of the transmitter acetylcholine (ACh) in the synaptic cleft. Overstimulation of cholinergic receptors (muscarinic and nicotinic) by excessive amounts of ACh causes several health problems and may even cause death. Reversible AChE inhibitors play an important role in prophylaxis against nerve agents. The presented study investigated whether 7-methoxytacrine (7-MEOTA) and 7-MEOTA-donepezil derivatives can act as central and peripheral reversible AChE inhibitors and simultaneously antagonize muscarinic and nicotinic receptors. The possible mechanism of action was studied on cell cultures (patch clamp technique, calcium mobilization assay) and on isolated smooth muscle tissue (contraction study). Furthermore, the kinetics of the compounds were also examined. CNS availability was predicted by determining the passive blood-brain barrier penetration estimated via a modified PAMPA assay. In conclusion, this study provides promising evidence that the new synthesized 7-MEOTA-donepezil derivatives have the desired anticholinergic effect; they can inhibit AChE, and nicotinic and muscarinic receptors in the micromolar range. Furthermore, they seem to penetrate readily into the CNS. However, their real potency and benefit must be verified by in vivo experiments.
Keywords: Indans; Donepezil; Cells, Cultured; Muscarinic Antagonists; zvířata; Rats; piperidiny; donepezil; mužské pohlaví; indany; nikotinoví antagonisté; Nicotinic Antagonists; Piperidines; Rats, Wistar; kultivované buňky; takrin; krysa rodu Rattus; Cholinergic Antagonists; Dose-Response Relationship, Drug; potkani Wistar; cholinergní antagonisté; Muscle Fibers, Skeletal; antagonisté muskarinových receptorů; vztah mezi dávkou a účinkem léčiva; Animals; Male; kosterní svalová vlákna; Tacrine